Indigenous Peoples and Internal Displacement: A Legal No Man's Land? - Musgrave,Jack (2020)
“Cultural identity is closely linked to their ancestral lands. If they are deprived of them, by means of forced displacement, it seriously affects their cultural identity, and finally, their very right to life lato sensu...” (Sawhoyamaxa Indigenous Community v. Paraguay) In the last five decades a movement calling for the protection of indigenous peoples’ rights has precipitated in a wave of international human rights law that attempts to mitigate against the disintegration of indigenous peoples’ culture caused by external agitators. Occurrences of outside agitators on indigenous communities has resulted in an increase in internal displacement. During internal displacement indigenous peoples find themselves in a double-bind of vulnerability. Firstly, vulnerable to human rights abuses as a direct result of internal displacement, and secondly, they are marginalised, excluded from consultation and assistance, and denied cultural expression due to long-standing structural discrimination. As such, internal displacement can lead to cultural disintegration, most prominently in situations of forced eviction and protracted displacement. The safety net of legal protection for indigenous people during internal displacement is stunted within international human rights law. The Guiding Principles on Internal Displacement (GPID or Guiding Principles) represents the foremost attempt at international law to uphold human rights during internal displacement, but in many respects, is the master of its own undoing. As such, the first part of this thesis will determine the scope of these Guiding Principles as they intersect with indigenous peoples’ rights, and then examine these against the Declaration on the Rights of Indigenous Peoples (UNDRIP) and the International Labour Organization Convention Concerning Indigenous and Tribal Peoples in Independent Countries 1989 (ILO Convention no. 169). This analysis will traverse the legal landscape for the human rights norms that seeks to protect indigenous peoples during internal displacement, and ultimately will identify the extent to which a legal ‘no man’s land’ exists. The second part of this thesis will put into focus the developments of indigenous peoples’ rights flourishing within the regional jurisdiction of the Organization of American States (OAS), referencing case law and advisory opinions which assert justiciable rights for indigenous peoples. Using reasoning by analogy, the jurisprudence of the Inter-American Court of Human Rights (IACtHR) will lay claim to sui generis rights for indigenous peoples in all instances of internal displacement, not limited to the most common occurrence of forced eviction but to include internal displacement induced by conflict, generalised violence, disasters and climate change. The legal basis for this rests upon indigenous peoples’ cultural and spiritual connection to their ancestral land, placing them in a unique ‘genus’ as rights holders. To strengthen this claim, it will be argued that ILO Convention no. 169 and UNDRIP operate in the same legal space, which is integrative, compatible and harmonious with the jurisprudential developments of the IACtHR. In light of the findings of this thesis, a case study on conflict in Colombia will be presented, which endorses a ‘realist’ and pro homine methodology to offer one mode of application for the rights of indigenous peoples during internal displacement.
Keywords: Indigenous peoples; human rights; internal displacement; Guiding Principles on Internal Displacement; UNDRIP; ILO Convention no. 169; Colombia